Objektivitas Sumber Daya Dosen Menggunakan Metode Weight Product - Deri Marse Putra; Gunadi Widi Nurcahyo (SAFE-Network, 2020)
Lecturers as one of the human resources who have an important role in higher education activities need to be maintained the quality of their performance. One of the activities carried out is evaluating and ranking lecturers to improve the quality of performance. There needs to be a Decision Support System that can help in assessing and evaluating lecturer performance. One method in decision support is the Weight Product Method. The purpose of this research is to create a decision support system to determine the best lecturers and rank of each lecturer. The subjects of this study were lecturers at Putra Indonesia University YPTK Padang using a data sample of 5 lecturers. Data collection techniques used in this study were observation and interviews. Comparison of the results of calculations carried out manually with the results of calculations using the Weight Product method of 5 sample data used found the best lecturer with a vector V value of 0.0819. This decision support system was created using the PHP programming language and MySQL database. So that this research is more efficient because the time required in the calculation is shorter and produces the best lecturer choice that matches the criteria.